The Right to Water in Jakarta: Limitation in a Sinking City - Ahmad Risyad Sumartapraja; Diajeng Wulan Christianti (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2022)
Unsustainable groundwater extraction in Jakarta has resulted in the subsidence of its land. Said effect had prompted the Regional Government to limit groundwater extraction. Consequently, the limitation threatens Jakarta residents’ minimum core enjoyment of the Human Right to Water (HRtW). People who live in coastal areas are the most affected. Northern Jakarta have considered the limitation as a burden that force them to spend more on necessities. Since there are no safeguards nor alternatives and that the limitation is from the Regional Government is disproportionate, this study argues that there is a violation of Jakarta residents’ Human Right to Water since their access towards water has been impeded, especially in areas without piped water. The Human Right to Water is a fundamental right, a foundation of the enjoyment of other rights. Like other human rights, it can be limited if the alternatives have already been installed. This study argues that, in the case of Jakarta, the safeguards that are supposed to be put into place is the progressive realization of Human Right to Water. It is the installation of a holistic piped water network. Indonesia has an obligation to provide piped water as a safeguard to its limitations otherwise international human rights law will be violated. DOI: https://doi.org/10.22304/pjih.v9n1.a3